2019
DOI: 10.3171/2018.6.jns172605
|View full text |Cite
|
Sign up to set email alerts
|

ACE-inhibitors: a preventive measure for bone flap resorption after autologous cranioplasty?

Abstract: OBJECTIVEDecompressive craniectomy (DC) is an established treatment for refractory intracranial hypertension. It is usually followed by autologous cranioplasty (AC), the reinsertion of a patient’s explanted bone flap. A frequent long-term complication of AC is bone flap resorption (BFR), which results in disfigurement as well as loss of the protective covering of the brain. This study investigates risk factors for BFR after AC, including medical conditions and antihypertensive drug therapies, with a focus on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…A possible contamination and subsequent low-grade infection with Propionibacterium acnes has been discussed as a potential risk factor as well [6,37]. Schütz et al were further able to show that hypertensive patients treated with ACE inhibitors had a lower ABR rate than patients treated with other antihypertensive medication or patients who do not suffer from arterial hypertension [35].…”
Section: Introductionmentioning
confidence: 99%
“…A possible contamination and subsequent low-grade infection with Propionibacterium acnes has been discussed as a potential risk factor as well [6,37]. Schütz et al were further able to show that hypertensive patients treated with ACE inhibitors had a lower ABR rate than patients treated with other antihypertensive medication or patients who do not suffer from arterial hypertension [35].…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to fully understand the relationship between lisinopril and bone healing, and to determine the mechanisms by which lisinopril may affect bone healing. [13][14][15][16][17][18] There has been some research on the potential effects of lisinopril on the CD34 bone healing marker. CD34 is a protein that is expressed by cells called mesenchymal stem cells, which are involved in tissue repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] BFR can lead to weakening, loosening and significant disintegration of the implanted autologous bone, which eventually results in loss of the bone coverage. [ 13 ] Revision surgery with replacement of synthetic material is necessary in severe cases of BFR and second surgery could be associated with higher expenses and poor clinical outcomes. [ 14 , 15 ] It would be reasonable to identify high-risk group that might suffer BFR and take preventive measures or choose alloplastic material cranioplasty for those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have found that younger age, bone flap fragmentations, and hydrocephalus shunt implantation to be associated with higher incidence of BFR. [ 11 , 16 18 ] Other potential risk factors, such as bone flap size, preservation of bone flap, and time interval between DC and cranioplasty [ 13 , 17 , 19 , 20 ] need to be assessed in a systematic approach. Therefore, we will undertake a systematic review and meta-analysis of studies presented data on risk factors for BFR requiring a second surgery after autologous cranioplasty.…”
Section: Introductionmentioning
confidence: 99%